Current Communication Technologies: An Overview - Kumar, Ashok; L., Udaya Sankar (DESIDOC Journal of Library & Information Technology, 2002)
Like most of the current interdisciplinary technologies, advances in computer and communication are influencing many different areas such as printing, photography and mass communication. As a reeult of these developments, in future, one may read newspaper on computer screen using electronic mail, use high definition or digital TV, filmless cameras, and telecommute to work. http://dx.doi.org/10.14429/dbit.12.3.3057